Nauczanie słuchaczy wojskowych słownictwa związanego z prawem konfliktów zbrojnych - Sylwia, Filipczuk-Rosińska (Investigationes Linguisticae, 2016)
This article is to present teaching methods adopted to develop lessons aimed at teaching vocabulary connected with LOAC (Law of Armed Conflict) to military personnel. Topics taken into consideration include: conduct of hostilities, prisoners of war (POW) and special signs. The presented exercises have been based on authentic materials such as: the Hague Convention, Geneva Conventions with additional protocols and rules of engagement cards. Additionally, the skills of speaking, reading and writing will be integrated. The exercises have already been conducted with professional soldiers as well as cadets at the Polish Air Force Academy in Dęblin. “The LOAC arises from a desire among civilized nations to prevent unnecessary suffering and destruction while not impeding the effective waging of war. A part of public international law, LOAC regulates the conduct of armed hostilities. It also aims to protect civilians, prisoners of war, the wounded, sick, and shipwrecked. LOAC applies to international armed conflicts and in the conduct of military operations and related activities in armed conflict, however such conflicts are characterized”. Rod Powers, US military expert